Association of surgeon volume and hospital volume with the outcome of patients receiving definitive surgery for colorectal cancer: A nationwide population‐based study. Issue 16 (17th April 2015) - Liu, Chia‐Jen; Chou, Yiing‐Jenq; Teng, Chung‐Jen; Lin, Chun‐Chi; Lee, Yu‐Ting; Hu, Yu‐Wen; Yeh, Chiu‐Mei; Chen, Tzeng‐Ji; Huang, Nicole
<x xml:space="preserve">Abstract</x> BACKGROUND Patients with colorectal cancer (CRC) who undergo cancer surgeries with higher‐volume providers may have better outcomes. The current debate focuses on whether it is hospital volume or surgeon volume that matters more. METHODS The authors conducted a nationwide population‐based study in Taiwan that enrolled all patients who underwent definitive surgery for newly diagnosed CRC between 2005 and 2011. All patients were divided into 4 quartiles according to hospital and surgeon volume. The main outcome was the 5‐year mortality rate, which was analyzed using a frailty model for Cox regression. The authors also conducted fixed and random effects multivariate regression models to examine short‐term outcomes and resource use, including operative mortality, hospital stay, emergency department visits within 30 days, and medical expenses. Analyses were adjusted for patient and provider characteristics. RESULTS A total of 61, 728 patients with CRC were included in the current study. The 5‐year mortality rates were 38.7%, 32.8%, 32.0%, and 29.1% in descending order of hospital volume quartiles and were 41.4%, 34.1%, 29.8%, and 27.4% in descending order of surgeon volume quartiles. After adjustment for the individual and provider characteristics, surgeon volume, but not hospital volume, remained a significantly predictive factor of death (P<.001). In addition, those patients with CRC who underwent definitive surgeries performed by higher‐volume surgeons had a relatively lower risk of operative mortality, shorter hospital length of stay, and lower medical expenses. CONCLUSIONS Patients with CRC who underwent definitive surgery performed by higher‐volume providers were found to have better outcomes. Surgeon volume may play a more important role than hospital volume. Cancer 2015;121:2782‐2790. © 2015 American Cancer Society